Cas12a-based one-pot SNP detection with high accuracy - Hong-Xia Zhang; Caixiang Zhang; Shuhan Lu; Xiaohan Tong; Kun Zhang; Hao Yin; Ying Zhang (Cell Insight, 2023)
CRISPR-Cas12a based one-pot detection system has been used in nucleic acid detection and diagnosis. However, it is not sensitive enough to distinguish single nucleotide polymorphisms (SNP), which has greatly restricted its application. To overcome these limitations, we engineered a LbCas12a variant with enhanced sensitivity against SNP, named seCas12a (sensitive Cas12a). SeCas12a-based one-pot SNP detection system is a versatile platform that could use both canonical and non-canonical PAM, and was almost not limited by mutation types to distinguish SNPs located between position 1 to 17. The use of truncated crRNA further improved SNP specificity of seCas12a. Mechanistically, we found only when the cis-cleavage was at low level between 0.01min−1 and 0.0006 min−1, a good signal-to-noise ratio can be achieved in one-pot test. SeCas12a-based one-pot SNP detection system was applied to detect pharmacogenomic SNPs in human clinical samples. Of thirteen donors tested in two different SNPs, the seCas12a mediated one-pot system could faithfully detect the SNPs in 30 min with 100% accuracy.